A plastic pipe containing plant fiber and preparation method thereof
By using nanosilica in plastic pipes to wrap modified materials such as maleic anhydride grafted cellulose and chlorinated polyethylene-epoxide soybean oil blends, the problem of insufficient mechanical properties and environmental protection of plastic pipes is solved. Higher mechanical properties and lower environmental pollution are achieved.
Patent Information
- Application Number
- CN202411612957.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-11-13
AI Technical Summary
The existing plastic pipes have shortcomings in terms of performance and environmental protection, including insufficient mechanical properties and large environmental pollution.
Plastic pipes containing plant fibers are used to wrap materials such as maleic anhydride grafted cellulose and chlorinated polyethylene-epoxide soybean oil blends through nano-silica to improve the mechanical and environmentally friendly properties of the pipes.
It significantly improves the mechanical and environmental performance of the pipeline, including increasing tensile strength, fracture extension rate, impact strength and thermal deformation temperature, while reducing the release of volatile organic compounds.
Smart Images

Figure CN119144099B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of pipelines, and in particular to a plastic pipeline containing plant fibers and a preparation method thereof. Background Art
[0002] Plastic pipes have been widely used in construction, municipal administration, agriculture, industry and other fields since the mid-20th century. They have quickly become popular due to their light weight, low cost, corrosion resistance and easy installation. Common plastic pipe materials include polyvinyl chloride (PVC), polyethylene (PE), polypropylene (PP), etc. These materials have good chemical stability and can resist corrosion from a variety of acids, alkalis and chemical solvents, extending the service life of the pipes. At the same time, the inner wall of the plastic pipe is smooth, the water flow resistance is small, and the transportation efficiency is high. Compared with traditional metal pipes, plastic pipes are light in weight, easy to transport and install, and can significantly reduce engineering costs.
[0003] However, with the extension of usage time and the improvement of environmental awareness, some shortcomings of plastic pipes have gradually emerged. First, the strength and rigidity of plastic pipes are not as good as metal pipes, and they are easy to deform or break under high pressure or high temperature environment. Secondly, the thermal expansion coefficient of plastic pipes is large, and temperature changes will cause the pipes to expand and contract significantly, affecting the service life and sealing performance. Furthermore, some plastic pipe materials will age and become brittle under direct sunlight, reducing the service life.
[0004] From an environmental perspective, plastic pipes have more problems. Harmful gases are emitted during the production process, posing a threat to the environment and human health. During use, certain plastic additives will slowly precipitate, polluting the water quality being transported. More seriously, plastic pipes are difficult to degrade and will remain in the environment for a long time after being scrapped, causing white pollution. Low recycling rates are also a major problem. Most waste plastic pipes are eventually landfilled or incinerated, increasing the burden on the environment.
[0005] In addition, plastic pipes are prone to burn and release toxic gases during fires, increasing the risk of fire. Some plastic pipes also have shortcomings such as insufficient impact resistance and poor wear resistance, and perform poorly in specific application scenarios. In recent years, in order to improve the performance of plastic pipes, the industry has developed a variety of modified materials and composite materials, such as PE-RT and PEX, but the cost is high and the environmental protection problem has not been fundamentally solved. Summary of the invention
[0006] (1) Technical issues to be resolved
[0007] The purpose of the present invention is to provide a plastic pipe containing plant fibers and a preparation method thereof, so as to solve the deficiencies of existing plastic pipes in terms of performance and environmental protection, especially to improve the mechanical properties of the pipe and reduce environmental pollution.
[0008] (2) Technical solution
[0009] To achieve the above object, on the one hand, the present invention provides a plastic pipe containing plant fibers, comprising the following raw materials in parts by weight: 35-50 parts of PVC resin, 5-15 parts of modified plant fibers, 0.6-1.0 parts of zinc stearate, 0.5-1.5 parts of calcium stearate, 0.3-0.8 parts of polyethylene wax, 0.1-0.3 parts of 2,6-di-tert-butyl-p-cresol, and 0.2-0.5 parts of acrylic acid;
[0010] The modified plant fiber is nano-silicon dioxide wrapped maleic anhydride grafted cellulose, and the surface of the modified plant fiber has hydroxyl and carboxyl groups.
[0011] Furthermore, a plastic pipe containing plant fibers further comprises, by weight: 3 to 8 parts of a chlorinated polyethylene-epoxidized soybean oil blend;
[0012] The chlorinated polyethylene-epoxidized soybean oil blend has a two-phase structure with a continuous phase and a dispersed phase.
[0013] Furthermore, the preparation method of the modified plant fiber comprises:
[0014] S11. drying the cellulose in an oven at 60-65° C. for 12-24 hours to obtain dry cellulose;
[0015] S12. Add dry cellulose and N,N-dimethylformamide to a three-necked round-bottom flask, stir and heat to 80°C for 1 to 1.5 hours to obtain a first mixed solution;
[0016] S13. Add maleic anhydride and benzoyl peroxide to the first mixed solution, raise the temperature to 90-100° C. under nitrogen protection, and react for 4-5 hours to obtain a second mixed solution;
[0017] S14. After the reaction is completed, the second mixed solution is cooled to room temperature, ethanol is added to obtain a precipitated product, the precipitated product is repeatedly washed with ethanol to obtain a washed precipitated product, and the washed precipitated product is vacuum dried at 50-60° C. for 12-24 h to obtain maleic anhydride grafted cellulose;
[0018] S15. The maleic anhydride grafted cellulose was dispersed in a mixed solution of ethanol and deionized water, and ultrasonically treated for 30 to 40 minutes to obtain a dispersed cellulose suspension;
[0019] S16. In another container, mix tetraethyl orthosilicate, ethanol and 28% ammonia water and stir for 15 to 20 minutes to obtain a uniform sol;
[0020] S17. Slowly adding the uniform sol to the dispersed cellulose suspension, stirring the reaction at room temperature for 4 to 5 hours to obtain a third mixed solution;
[0021] S18. The third mixed solution is centrifuged to obtain a product, the product is repeatedly washed with ethanol and deionized water to obtain a washed product, and the washed product is vacuum dried at 50-60° C. for 12-24 hours to obtain nano-silica-encapsulated maleic anhydride grafted cellulose.
[0022] Furthermore, the preparation method of the chlorinated polyethylene-epoxidized soybean oil blend comprises:
[0023] S21. Weigh chlorinated polyethylene, add tetrahydrofuran, and stir at room temperature for 4 h until completely dissolved to obtain a chlorinated polyethylene solution;
[0024] S22. The chlorinated polyethylene solution was transferred to a three-necked flask, and the pre-weighed epoxidized soybean oil and 0.5-0.8% distearyl thiodipropionate were added, and the mixture was stirred in a water bath at 50-60°C at a speed of 200-300 rpm for 2 h to obtain a mixed solution;
[0025] S23. Pour the mixed solution into a glass culture dish and volatilize it naturally at room temperature for 24 to 36 hours to obtain a preliminarily dried film. Dry the preliminarily dried film in a vacuum drying oven at 40 to 50° C. for 48 to 56 hours to obtain a dried film.
[0026] S24. The dried film is placed at room temperature for 24 to 36 hours, and then peeled and cut to obtain a blended film of a desired size, wherein the blended film is a chlorinated polyethylene-epoxidized soybean oil blend.
[0027] On the other hand, based on the same inventive concept, the present invention also provides a method for preparing a plastic pipe containing plant fibers, which is applied to the plastic pipe containing plant fibers, and comprises the following steps:
[0028] S31. Preparing modified plant fibers;
[0029] S32. Preparation of chlorinated polyethylene-epoxidized soybean oil blends;
[0030] S33. Drying the PVC resin and the modified plant fiber at 50-60°C for 4-5 hours, and drying the zinc stearate, calcium stearate, polyethylene wax, 2,6-di-tert-butyl-p-cresol, acrylic acid and chlorinated polyethylene-epoxidized soybean oil blend at 50-60°C for 1-2 hours;
[0031] S34. Weigh PVC resin, modified plant fiber, zinc stearate, calcium stearate, polyethylene wax, 2,6-di-tert-butyl-p-cresol, acrylic acid and chlorinated polyethylene-epoxidized soybean oil blend, add to a high-speed mixer, and mix at 80 to 90 ° C for 10 to 15 minutes to obtain a mixture;
[0032] S35. The mixture was added to a twin-screw extruder, and the feed zone was set to 140-150°C, the compression zone was set to 160-170°C, the homogenization zone was set to 170-180°C, the discharge zone was set to 175-185°C, the screw speed was set to 20-30 rpm, and the mixing time was set to 5-7 min to obtain a mixed product;
[0033] S36. The mixed product was added to a single screw extruder, and the feed zone was set to 150-160°C, the compression zone was set to 170-180°C, the metering zone was set to 180-190°C, the die was set to 185-195°C, and the screw speed was set to 15-25 rpm to obtain an extruded pipe;
[0034] S37. The extruded pipe is passed through a vacuum setting box, the cooling water temperature is 15-20°C, the cooling time is 1-3 minutes, and a cooled pipe is obtained. The cooled pipe is cut into the required length using an automatic cutting machine.
[0035] The mechanism of action of the above raw material components is as follows:
[0036] PVC resin: As the main matrix material, it provides the basic structure and performance of the pipe. PVC has good chemical stability, corrosion resistance and insulation.
[0037] Modified plant fiber: Cellulose provides reinforcement, improving the mechanical strength and rigidity of the pipe. Maleic anhydride grafting increases the compatibility of cellulose with the PVC matrix and improves the interface bonding. Nano-silica wrapping further enhances the interface bonding between the fiber and the matrix, while improving the dispersion and heat resistance of the fiber.
[0038] Chlorinated polyethylene-epoxidized soybean oil blend: Chlorinated polyethylene has good compatibility with PVC and increases the flexibility of the system. Epoxidized soybean oil acts as a plasticizer to improve the processability of the system while increasing the bio-based content. The blend form helps to disperse evenly and improve overall performance.
[0039] Zinc stearate: As a heat stabilizer, it can effectively capture the hydrogen chloride released during the degradation of PVC, preventing hydrogen chloride from further catalyzing the degradation of PVC, thereby improving the thermal stability of the pipe. Secondly, zinc stearate also has a lubricating effect. During the processing, it can reduce the friction between PVC and processing equipment, improve the fluidity of the material, and help improve the surface smoothness and processing efficiency of the pipe. In addition, zinc stearate can also improve the compatibility between PVC and plant fibers, promote the uniform dispersion of the two, and thus enhance the overall performance of the composite material.
[0040] Calcium stearate: acts as a lubricant to improve processing fluidity and prevent materials from adhering to processing equipment.
[0041] Polyethylene wax: external lubricant, improves melt fluidity and enhances surface gloss.
[0042] 2,6-Di-tert-Butyl-p-cresol: Prevents oxidative degradation of materials during processing and use, and improves long-term performance.
[0043] Acrylic acid: Improves melt fluidity, helps improve production efficiency and product surface quality.
[0044] (3) Beneficial effects
[0045] Compared with the prior art, the present invention has the following beneficial effects:
[0046] 1. The plant fibers encapsulated by nano-silica and grafted with maleic anhydride significantly improved their compatibility and dispersibility with the PVC matrix.
[0047] 2. The chlorinated polyethylene-epoxidized soybean oil blend constructs a multi-level barrier system, which effectively prolongs the diffusion path of VOCs, thereby inhibiting the release of VOCs and improving the environmental performance of the product.
[0048] 3. The introduction of epoxidized soybean oil not only improves the processing properties of the material, but also reduces the demand for traditional petroleum-based plasticizers. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 This is a SEM image of the modified plant fiber of Example 1 of the present invention. DETAILED DESCRIPTION
[0050] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0051] The test equipment and preparations of the examples described below are as follows:
[0052] Electronic balance (Sartorius, Germany), electric blast constant temperature dryer (Shanghai Fomar Experimental Equipment), stainless steel reactor (Shanghai Laibei), electric constant temperature water bath (Jiangsu Kedao), rotary evaporator (Shanghai Darlo Scientific Instrument), pulverizer (Shandong Tianfang Machinery), magnetic stirrer (Shanghai Meiyingpu), ball mill (Henan Zhengkuang), twin-screw extruder (Shanghai Zhouxing), single-screw extruder (Nanjing Cologne Will), vacuum setting box (Qingdao Kunlun Haisu), thermal desorption-gas chromatography-mass spectrometry (PerkinElmer); epoxidized soybean oil was purchased from Shandong Hongyunchang Chemical Technology Co., Ltd., and chemicals and reagents were purchased from Sigma-Aldrich.
[0053] Example 1: This example discloses a plastic pipe containing plant fibers, comprising the following raw materials in parts by weight: 40 parts of PVC resin, 12 parts of modified plant fibers, 0.8 parts of zinc stearate, 1 part of calcium stearate, 0.5 parts of polyethylene wax, 0.2 parts of 2,6-di-tert-butyl-p-cresol, and 0.4 parts of acrylic acid; the modified plant fibers are nano-silica-wrapped maleic anhydride-grafted cellulose, and the modified plant fibers have hydroxyl and carboxyl groups on their surfaces.
[0054] The plant fiber-containing plastic pipe further comprises, by weight, 6 parts of a chlorinated polyethylene-epoxidized soybean oil blend; the chlorinated polyethylene-epoxidized soybean oil blend has a two-phase structure of a continuous phase and a dispersed phase.
[0055] PVC resin as a base material provides the basic strength and chemical stability required for pipelines. In order to further improve the performance and environmental protection of pipelines, nano-silica-encapsulated maleic anhydride-grafted cellulose is introduced, such as Figure 1 As shown in the figure, the nano-scale silica particle coating on the outside of the plant fiber can prevent the fiber from agglomerating in PVC. Without this coating, the plant fiber will tend to gather together and form clumps, which will reduce the reinforcement effect of the fiber. The nano-scale silica particle coating on the outside of the plant fiber can also increase the bonding strength between the fiber and PVC without generating cracks or gaps. Maleic anhydride grafting adds carboxyl and hydroxyl groups to the fiber surface. These two groups can form hydrogen bonds and dipole-dipole interactions with PVC, allowing the fiber and PVC to bind more tightly, so that the plant fiber can be evenly dispersed in PVC and form a very strong bond with PVC. When the pipeline is under pressure, these fibers can effectively disperse and transmit stress, greatly improving the strength and rigidity of the pipeline.
[0056] During the mixing process, the chlorinated polyethylene-epoxidized soybean oil blend forms a unique two-phase structure due to the differences in polarity and molecular weight between the chlorinated polyethylene and the epoxidized soybean oil: the chlorinated polyethylene forms a continuous phase, while the epoxidized soybean oil forms a dispersed phase. This structure forms an "interpenetrating network structure", which prolongs the diffusion path of volatile organic compounds (VOCs), and constructs a dense barrier system through the reaction of the epoxy groups of the epoxidized soybean oil with the chlorine atoms on the chlorinated polyethylene chain and the cross-linking between the epoxidized soybean oil molecules, further preventing the release of VOCs.
[0057] In addition, chlorinated polyethylene has good compatibility with the PVC matrix, which enhances the overall structural stability of the material. Epoxidized soybean oil can also generate affinity with modified plant fibers through its polar groups, form chemical bonds between epoxy groups and hydroxyl groups on the fiber surface, and generate physical entanglements with PVC molecules through long-chain structures, which optimizes the interface bonding. The optimized interface bonding ensures that stress can be effectively transferred from PVC to the fiber, giving full play to the reinforcing effect of the fiber, thereby improving the mechanical properties of the material.
[0058] The introduction of epoxidized soybean oil also has a plasticizing effect, which improves the processing properties of the material. Due to the use of plant-derived epoxidized soybean oil, the demand for traditional petroleum-based plasticizers is reduced, making the entire formula more environmentally friendly.
[0059] The preparation method of the modified plant fiber comprises:
[0060] S11. drying the cellulose in an oven at 60-65° C. for 12-24 hours to obtain dry cellulose;
[0061] S12. Add dry cellulose and N,N-dimethylformamide to a three-necked round-bottom flask, stir and heat to 80°C for 1 to 1.5 hours to obtain a first mixed solution;
[0062] S13. Add maleic anhydride and benzoyl peroxide to the first mixed solution, raise the temperature to 90-100° C. under nitrogen protection, and react for 4-5 hours to obtain a second mixed solution;
[0063] S14. After the reaction is completed, the second mixed solution is cooled to room temperature, ethanol is added to obtain a precipitated product, the precipitated product is repeatedly washed with ethanol to obtain a washed precipitated product, and the washed precipitated product is vacuum dried at 50-60° C. for 12-24 h to obtain maleic anhydride grafted cellulose;
[0064] S15. The maleic anhydride grafted cellulose was dispersed in a mixed solution of ethanol and deionized water, and ultrasonically treated for 30 to 40 minutes to obtain a dispersed cellulose suspension;
[0065] S16. In another container, mix tetraethyl orthosilicate, ethanol and 28% ammonia water and stir for 15 to 20 minutes to obtain a uniform sol;
[0066] S17. Slowly adding the uniform sol to the dispersed cellulose suspension, stirring the reaction at room temperature for 4 to 5 hours to obtain a third mixed solution;
[0067] S18. The third mixed solution is centrifuged to obtain a product, the product is repeatedly washed with ethanol and deionized water to obtain a washed product, and the washed product is vacuum dried at 50-60° C. for 12-24 hours to obtain nano-silica-encapsulated maleic anhydride grafted cellulose.
[0068] The preparation method of the chlorinated polyethylene-epoxidized soybean oil blend comprises:
[0069] S21. Weigh chlorinated polyethylene, add tetrahydrofuran, and stir at room temperature for 4 h until completely dissolved to obtain a chlorinated polyethylene solution;
[0070] S22. The chlorinated polyethylene solution was transferred to a three-necked flask, and the pre-weighed epoxidized soybean oil and 0.5-0.8% distearyl thiodipropionate were added, and the mixture was stirred in a water bath at 50-60°C at a speed of 200-300 rpm for 2 h to obtain a mixed solution;
[0071] S23. Pour the mixed solution into a glass culture dish and volatilize it naturally at room temperature for 24 to 36 hours to obtain a preliminarily dried film. Dry the preliminarily dried film in a vacuum drying oven at 40 to 50° C. for 48 to 56 hours to obtain a dried film.
[0072] S24. The dried film is placed at room temperature for 24 to 36 hours, and then peeled and cut to obtain a blended film of a desired size, wherein the blended film is a chlorinated polyethylene-epoxidized soybean oil blend.
[0073] A method for preparing a plastic pipe containing plant fibers, which is applied to the plastic pipe containing plant fibers, comprises the following steps:
[0074] S31. Preparing modified plant fibers;
[0075] S32. Preparation of chlorinated polyethylene-epoxidized soybean oil blends;
[0076] S33. Drying the PVC resin and the modified plant fiber at 50-60°C for 4-5 hours, and drying the zinc stearate, calcium stearate, polyethylene wax, 2,6-di-tert-butyl-p-cresol, acrylic acid and chlorinated polyethylene-epoxidized soybean oil blend at 50-60°C for 1-2 hours;
[0077] S34. Weigh PVC resin, modified plant fiber, zinc stearate, calcium stearate, polyethylene wax, 2,6-di-tert-butyl-p-cresol, acrylic acid and chlorinated polyethylene-epoxidized soybean oil blend, add to a high-speed mixer, and mix at 80 to 90 ° C for 10 to 15 minutes to obtain a mixture;
[0078] S35. The mixture was added to a twin-screw extruder, and the feed zone was set to 140-150°C, the compression zone was set to 160-170°C, the homogenization zone was set to 170-180°C, the discharge zone was set to 175-185°C, the screw speed was set to 20-30 rpm, and the mixing time was set to 5-7 min to obtain a mixed product;
[0079] S36. The mixed product was added to a single screw extruder, and the feed zone was set to 150-160°C, the compression zone was set to 170-180°C, the metering zone was set to 180-190°C, the die was set to 185-195°C, and the screw speed was set to 15-25 rpm to obtain an extruded pipe;
[0080] S37. The extruded pipe is passed through a vacuum setting box, the cooling water temperature is 15-20°C, the cooling time is 1-3 minutes, and a cooled pipe is obtained. The cooled pipe is cut into the required length using an automatic cutting machine.
[0081] Example 2: This example discloses a plastic pipe containing plant fibers, comprising the following raw materials in parts by weight: 35 parts of PVC resin, 5 parts of modified plant fibers, 0.6 parts of zinc stearate, 0.5 parts of calcium stearate, 0.3 parts of polyethylene wax, 0.1 parts of 2,6-di-tert-butyl-p-cresol, and 0.2 parts of acrylic acid; the modified plant fibers are nano-silica-wrapped maleic anhydride-grafted cellulose, and the modified plant fibers have hydroxyl and carboxyl groups on their surfaces.
[0082] The plant fiber-containing plastic pipe further comprises, by weight, 3 parts of a chlorinated polyethylene-epoxidized soybean oil blend; the chlorinated polyethylene-epoxidized soybean oil blend has a two-phase structure of a continuous phase and a dispersed phase.
[0083] The preparation method of the modified plant fiber and the chlorinated polyethylene-epoxidized soybean oil blend in this embodiment is consistent with that in Example 1. The preparation method of a plastic pipe containing plant fiber in this embodiment is consistent with that in Example 1.
[0084] Example 3: This example discloses a plastic pipe containing plant fibers, comprising the following raw materials in parts by weight: 50 parts of PVC resin, 15 parts of modified plant fibers, 1.0 parts of zinc stearate, 1.5 parts of calcium stearate, 0.8 parts of polyethylene wax, 0.3 parts of 2,6-di-tert-butyl-p-cresol, and 0.5 parts of acrylic acid; the modified plant fibers are nano-silica-wrapped maleic anhydride-grafted cellulose, and the modified plant fibers have hydroxyl and carboxyl groups on their surfaces.
[0085] The plant fiber-containing plastic pipe further comprises, by weight, 8 parts of a chlorinated polyethylene-epoxidized soybean oil blend; the chlorinated polyethylene-epoxidized soybean oil blend has a two-phase structure of a continuous phase and a dispersed phase.
[0086] The preparation method of the modified plant fiber and the chlorinated polyethylene-epoxidized soybean oil blend in this embodiment is consistent with that in Example 1. The preparation method of a plastic pipe containing plant fiber in this embodiment is consistent with that in Example 1.
[0087] Example 4: This example discloses a plastic pipe containing plant fibers, comprising the following raw materials in parts by weight: 42 parts of PVC resin, 10 parts of modified plant fibers, 0.8 parts of zinc stearate, 1 part of calcium stearate, 0.5 parts of polyethylene wax, 0.2 parts of 2,6-di-tert-butyl-p-cresol, and 0.3 parts of acrylic acid; the modified plant fibers are nano-silica-wrapped maleic anhydride-grafted cellulose, and the modified plant fibers have hydroxyl and carboxyl groups on their surfaces.
[0088] The plant fiber-containing plastic pipe further comprises, by weight, 5 parts of a chlorinated polyethylene-epoxidized soybean oil blend; the chlorinated polyethylene-epoxidized soybean oil blend has a two-phase structure of a continuous phase and a dispersed phase.
[0089] The preparation method of the modified plant fiber and the chlorinated polyethylene-epoxidized soybean oil blend in this embodiment is consistent with that in Example 1. The preparation method of a plastic pipe containing plant fiber in this embodiment is consistent with that in Example 1.
[0090] Control group 1: This embodiment discloses a plastic pipe containing plant fiber, comprising the following raw materials in parts by weight: 40 parts of PVC resin, 12 parts of plant fiber, 0.8 parts of zinc stearate, 1 part of calcium stearate, 0.5 parts of polyethylene wax, 0.2 parts of 2,6-di-tert-butyl-p-cresol, and 0.4 parts of acrylic acid.
[0091] The plant fiber-containing plastic pipe further comprises, by weight, 6 parts of a chlorinated polyethylene-epoxidized soybean oil blend; the chlorinated polyethylene-epoxidized soybean oil blend has a two-phase structure of a continuous phase and a dispersed phase.
[0092] The preparation method of the plant fiber in this embodiment directly refers to the preparation method of the plant fiber in Example 1 without modification. The preparation method of the chlorinated polyethylene-epoxidized soybean oil blend in this embodiment is consistent with that in Example 1. The preparation method of a plastic pipe containing plant fiber in this embodiment is consistent with that in Example 1.
[0093] Control group 2: This embodiment discloses a plastic pipe containing plant fiber, comprising the following raw materials in parts by weight: 40 parts of PVC resin, 12 parts of modified plant fiber, 0.8 parts of zinc stearate, 1 part of calcium stearate, 0.5 parts of polyethylene wax, 0.2 parts of 2,6-di-tert-butyl-p-cresol, and 0.4 parts of acrylic acid; the modified plant fiber is nano-silica-wrapped maleic anhydride grafted cellulose, and the modified plant fiber has hydroxyl and carboxyl groups on its surface.
[0094] The plant fiber-containing plastic pipe further comprises, by weight: 6 parts of epoxidized soybean oil.
[0095] The preparation method of the modified plant fiber in this embodiment is consistent with that in Example 1. The preparation method of a plastic pipe containing plant fiber in this embodiment is consistent with that in Example 1.
[0096] Control group 3: This embodiment discloses a plastic pipe containing plant fiber, comprising the following raw materials in parts by weight: 40 parts of PVC resin, 12 parts of modified plant fiber, 0.8 parts of zinc stearate, 1 part of calcium stearate, 0.5 parts of polyethylene wax, 0.2 parts of 2,6-di-tert-butyl-p-cresol, and 0.4 parts of acrylic acid; the modified plant fiber is nano-silica-wrapped maleic anhydride grafted cellulose, and the modified plant fiber has hydroxyl and carboxyl groups on its surface.
[0097] The plant fiber-containing plastic pipe further comprises, by weight, 6 parts of chlorinated polyethylene.
[0098] The preparation method of the modified plant fiber in this embodiment is consistent with that in Example 1. The preparation method of a plastic pipe containing plant fiber in this embodiment is consistent with that in Example 1.
[0099] Control group 4: This embodiment discloses a plastic pipe containing plant fibers, comprising the following raw materials in parts by weight: 40 parts of PVC resin, 12 parts of maleic anhydride grafted plant fibers, 0.8 parts of zinc stearate, 1 part of calcium stearate, 0.5 parts of polyethylene wax, 0.2 parts of 2,6-di-tert-butyl-p-cresol, and 0.4 parts of acrylic acid;
[0100] The plant fiber-containing plastic pipe further comprises, by weight, 6 parts of a chlorinated polyethylene-epoxidized soybean oil blend; the chlorinated polyethylene-epoxidized soybean oil blend has a two-phase structure of a continuous phase and a dispersed phase.
[0101] The preparation method of the maleic anhydride grafted plant fiber in this embodiment directly refers to the preparation method of the plant fiber in Example 1, without nano-silicon dioxide encapsulation modification. The preparation method of the chlorinated polyethylene-epoxidized soybean oil blend in this embodiment is consistent with that in Example 1. The preparation method of a plastic pipe containing plant fiber in this embodiment is consistent with that in Example 1.
[0102] Control group 5: This embodiment discloses a plastic pipe containing plant fibers, comprising the following raw materials in parts by weight: 40 parts of PVC resin, 12 parts of modified plant fibers, 0.8 parts of zinc stearate, 1 part of calcium stearate, 0.5 parts of polyethylene wax, 0.2 parts of 2,6-di-tert-butyl-p-cresol, and 0.4 parts of acrylic acid;
[0103] The preparation method of the modified plant fiber in this embodiment is consistent with that in Example 1. The preparation method of a plastic pipe containing plant fiber in this embodiment is consistent with that in Example 1.
[0104] Control group 6: This embodiment discloses a plastic pipe containing plant fibers, comprising the following raw materials in parts by weight: 40 parts of PVC resin, 12 parts of nano-silicon dioxide-wrapped plant fibers, 0.8 parts of zinc stearate, 1 part of calcium stearate, 0.5 parts of polyethylene wax, 0.2 parts of 2,6-di-tert-butyl-p-cresol, and 0.4 parts of acrylic acid;
[0105] The plant fiber-containing plastic pipe further comprises, by weight, 6 parts of a chlorinated polyethylene-epoxidized soybean oil blend; the chlorinated polyethylene-epoxidized soybean oil blend has a two-phase structure of a continuous phase and a dispersed phase.
[0106] The preparation method of the nano-silica-coated plant fiber in this embodiment directly refers to the preparation method of the plant fiber in Example 1, without maleic anhydride grafting modification. The preparation method of the chlorinated polyethylene-epoxidized soybean oil blend in this embodiment is consistent with that in Example 1. The preparation method of a plastic pipe containing plant fiber in this embodiment is consistent with that in Example 1.
[0107] Test verification:
[0108] 1. Tensile performance test: The plastic pipes prepared in the embodiment group and the control group were cut into dumbbell-shaped specimens with a gauge length of 25 mm. They were conditioned at 23±2°C and 50±5%RH for 24 h before testing. The specimens were clamped on a tensile testing machine with a tensile speed of 50 mm / min set, and the maximum load and elongation at break were recorded.
[0109] 2. Impact performance test: The plastic pipes prepared in the embodiment group and the control group were cut into a length of 50±1mm, and a notch was made with a depth of 2mm and a tip radius of 0.25±0.05mm. The samples were placed on a support with the notch facing downward, the pendulum energy was adjusted to 4J, the pendulum was released for impact, and the absorbed energy was recorded.
[0110] 3. Heat deformation temperature test: The plastic pipes prepared in the embodiment group and the control group were cut into the following sizes: length 120±2 mm, width 10±0.2 mm, thickness 4±0.2 mm.
[0111] Pretreatment conditions: temperature: 23±2℃, relative humidity: 50±5%, time: at least 24h.
[0112] Place the sample on the support frame, support span: 100±1mm, ensure that the sample is placed horizontally, apply a load of 1.80MPa, ensure that the load is evenly applied to the center of the sample, heating rate: 120±10℃ / h, heating medium temperature uniformity: ±1℃, record data and record the temperature when the sample deflection reaches 0.32mm.
[0113] 3. VOCs release test: Use a 1m³ stainless steel or glass environmental chamber, clean it thoroughly with a detergent and then bake it at 80℃ for 4h; adjust the temperature of the environmental chamber to 23±2℃, the relative humidity to 50±5%, and the ventilation rate to 0.5±0.05 times / h; load the samples into the environmental chamber and seal it according to the actual use area ratio; use a Tenax sampling tube to collect 1L volume of gas samples at a flow rate of 100mL / min on the 1st, 3rd, 7th, 14th and 28th day after loading; use thermal desorption-gas chromatography-mass spectrometry for analysis, use HP-5MS or similar specification chromatographic columns, and use a heating program (initial temperature 40℃ for 5min, increase to 250℃ at 10℃ / min and hold for 5min) for detection; use the NIST spectral library to identify the compounds, use the internal standard method for quantitative analysis, and calculate the VOC release factor (μg / m²·h). The test at each time point needs to be analyzed in parallel, and all test conditions, processes and results must be fully recorded.
[0114]
[0115]
[0116] Through comprehensive analysis of the plastic pipe performance test and VOCs release test results of the embodiment group and the control group, it can be clearly seen that the embodiment group, especially embodiment 1, shows significant advantages in all indicators.
[0117] In terms of mechanical properties, the tensile strength of Example 1 reaches 46.5MPa, which is 37% higher than the average value of the control group; the elongation at break reaches 195%, which is 30.6% higher than the average value of the control group; the impact strength is 17.8kJ / m², which exceeds the average value of the control group by 57.2%; the heat deformation temperature is 85.5℃, which is 15.6% higher than the average value of the control group.
[0118] These data show that the mechanical properties and thermal stability of the pipe are significantly improved by adding the modified plant fiber and the chlorinated polyethylene-epoxidized soybean oil blend. Among them, Examples 1 to 4 all show better performance than the control group, which confirms the effectiveness of the modified formula.
[0119] In the VOCs release test, the embodiment group also showed good environmental protection characteristics. The initial VOCs release of Example 1 was 350μg / m²·h, which was only 51.5% of that of Control Group 1 and 58.8% of the average initial release of the control group; after 28 days, the release of Example 1 dropped to 65μg / m²·h, which was 41.9% of the average value of the control group; all samples of the embodiment group showed a trend of rapid decrease in VOCs release over time, and the decrease was much greater than that of the control group, which shows that the modified formula not only reduces the initial VOCs release, but also promotes the rapid emission of residual VOCs. By comparing the four embodiments, it can be found that the VOCs release levels of Examples 1 and 2 are generally lower than those of Examples 3 and 4, which is related to the optimal ratio of modified plant fiber and chlorinated polyethylene-epoxidized soybean oil blend in their formulas.
[0120] It is worth noting that in all test indicators, the control group 1 (unmodified plant fiber) performed the worst, especially in terms of VOCs emission. This further confirms the importance of modification treatment in improving product performance.
[0121] Control group 6 (using nano-silica encapsulated plant fibers and chlorinated polyethylene-epoxidized soybean oil blend) performed the best among the control groups, especially in terms of VOCs release control, which shows that the combination of nano-silica encapsulation and chlorinated polyethylene-epoxidized soybean oil blend does have a positive effect, but it is still inferior to the comprehensive modification effect of the embodiment group.
[0122] Finally, it should be noted that: Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A plastic pipe containing plant fibers, characterized in that: The invention comprises the following raw materials in parts by weight: 35-50 parts of PVC resin, 5-15 parts of modified plant fiber, 0.6-1.0 parts of zinc stearate, 0.5-1.5 parts of calcium stearate, 0.3-0.8 parts of polyethylene wax, 0.1-0.3 parts of 2,6-di-tert-butyl-p-cresol, 0.2-0.5 parts of acrylic acid, and 3-8 parts of chlorinated polyethylene-epoxidized soybean oil blend; the modified plant fiber is nano-silicon dioxide-wrapped maleic anhydride grafted cellulose, and the surface of the modified plant fiber has hydroxyl and carboxyl groups; the chlorinated polyethylene-epoxidized soybean oil blend has a two-phase structure of a continuous phase and a dispersed phase; The preparation method of the chlorinated polyethylene-epoxidized soybean oil blend comprises: S11. Weigh chlorinated polyethylene, add tetrahydrofuran, and stir at room temperature for 4h until completely dissolved to obtain a chlorinated polyethylene solution; S12. The chlorinated polyethylene solution was transferred to a three-necked flask, and the pre-weighed epoxidized soybean oil and 0.5-0.8% distearyl thiodipropionate were added, and the mixture was stirred in a water bath at 50-60°C at a speed of 200-300 rpm for 2 h to obtain a mixed solution; S13. Pour the mixed solution into a glass culture dish and volatilize it naturally at room temperature for 24 to 36 hours to obtain a preliminarily dried film. Dry the preliminarily dried film in a vacuum drying oven at 40 to 50° C. for 48 to 56 hours to obtain a dried film. S14. The dried film is placed at room temperature for 24 to 36 hours, peeled and cut to obtain a blended film of the desired size, wherein the blended film is a chlorinated polyethylene-epoxidized soybean oil blend; The preparation method of the modified plant fiber comprises: S21. drying the cellulose in an oven at 60-65° C. for 12-24 h to obtain dry cellulose; S22. Add dry cellulose and N,N-dimethylformamide to a three-necked round-bottom flask, stir and heat to 80°C for 1 to 1.5 hours to obtain a first mixed solution; S23. Add maleic anhydride and benzoyl peroxide to the first mixed solution, raise the temperature to 90-100° C. under nitrogen protection, and react for 4-5 hours to obtain a second mixed solution; S24. After the reaction is completed, the second mixed solution is cooled to room temperature, ethanol is added to obtain a precipitated product, the precipitated product is repeatedly washed with ethanol to obtain a washed precipitated product, and the washed precipitated product is vacuum dried at 50-60° C. for 12-24 h to obtain maleic anhydride grafted cellulose; S25. The maleic anhydride grafted cellulose was dispersed in a mixed solution of ethanol and deionized water, and ultrasonically treated for 30 to 40 minutes to obtain a dispersed cellulose suspension; S26. In another container, mix tetraethyl orthosilicate, ethanol and 28% ammonia water and stir for 15 to 20 minutes to obtain a uniform sol; S27. The uniform sol is slowly added to the dispersed cellulose suspension, and the reaction is stirred at room temperature for 4 to 5 hours to obtain a third mixed solution; S28. The third mixed solution is centrifuged to obtain a product, the product is repeatedly washed with ethanol and deionized water to obtain a washed product, and the washed product is vacuum dried at 50-60° C. for 12-24 hours to obtain nano-silica-encapsulated maleic anhydride grafted cellulose.
2. A method for preparing a plastic pipe containing plant fibers, which is used to prepare the plastic pipe containing plant fibers as claimed in claim 1, characterized in that: The method comprises the following steps: S31. Preparing modified plant fibers; S32. Preparation of chlorinated polyethylene-epoxidized soybean oil blends; S33. Drying the PVC resin and the modified plant fiber at 50-60°C for 4-5 hours, and drying the zinc stearate, calcium stearate, polyethylene wax, 2,6-di-tert-butyl-p-cresol, acrylic acid and chlorinated polyethylene-epoxidized soybean oil blend at 50-60°C for 1-2 hours; S34. Weigh PVC resin, modified plant fiber, zinc stearate, calcium stearate, polyethylene wax, 2,6-di-tert-butyl-p-cresol, acrylic acid and chlorinated polyethylene-epoxidized soybean oil blend, add to a high-speed mixer, and mix at 80 to 90 ° C for 10 to 15 minutes to obtain a mixture; S35. The mixture was added to a twin-screw extruder, and the feed zone was set to 140-150°C, the compression zone was set to 160-170°C, the homogenization zone was set to 170-180°C, the discharge zone was set to 175-185°C, the screw speed was set to 20-30 rpm, and the mixing time was set to 5-7 min to obtain a mixed product; S36. The mixed product was added to a single screw extruder, and the feed zone was set to 150-160°C, the compression zone was set to 170-180°C, the metering zone was set to 180-190°C, the die was set to 185-195°C, and the screw speed was set to 15-25 rpm to obtain an extruded pipe; S37. The extruded pipe is passed through a vacuum setting box, the cooling water temperature is 15-20°C, the cooling time is 1-3 minutes, and a cooled pipe is obtained. The cooled pipe is cut into the required length using an automatic cutting machine.
Citation Information
Patent Citations
Anti-impact anti-static modified polyvinyl chloride pipe
CN105733128A
High-strength and high-toughness composite material
CN106147067A